Analisis Pragmatik Variasi Kesantunan Tindak Tutur Terima Kasih Bahasa Jepang dalam Film Beautiful Life Karya Kitagawa Eriko - Akhmad Saifudin (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2010)
This study discusses the politeness in speech act of thankingin correlation to the Japanese situation and object structure of thanking. This study aims to identify and define the socio-cultural factor and politeness in speech act of thanking using pragmatics point of view. The writer uses Kitagawa Eriko’s Beautiful Life movie as the source of data. The result shows that the disclosure of speech act of thanking relies on the speech situation and object structure of thanking. The factors of speech situation are the context of event and the relationship among participants or ‘uchi/soto’. The factors of object structure of thanking are real or potential, major or minor, material or immaterial, asked or unasked kindness, and kindness which can lead to moral duty. Those factors affect the choice of the types of speech act of thanking. As a result, the socio-cultural factor that determines the speech variation is uchi/soto.Key words: Language politeness, Speech situation, Thanking object, Thanking speech act, Uchi/soto